KEUNIKAN PENDIDIKAN ISLAM DAN RELEVANSINYA TERHADAP FILSAFAT PENDIDIKAN ISLAM KONTEMPORER - Nur Aziza; Muhammad Sirozi (UIN Sumatera Utara Medan, 2024)
The uniqueness of Islamic education from the perspective of contemporary Islamic educational philosophy seeks to reconstruct Islamic education to be relevant to the challenges of the times. This study uses a qualitative method with a literature analysis approach. Data were collected from various sources, including books, journal articles, and official documents related to Islamic education and educational philosophy. The analysis was carried out by identifying the main themes that emerged in the literature, and linking them to the context of contemporary education. In this way, it is hoped that a deeper understanding of the uniqueness and excellence of Islamic education can be obtained. Islamic education has a uniqueness that distinguishes it from other education systems, especially in terms of approach and objectives. One of the main aspects of Islamic education is not only aimed at producing individuals who are intellectually intelligent, but also have character and noble morals. The excellence of Islamic education can be seen from various aspects, including curriculum, teaching methods, and social impacts. With the uniqueness and excellence of Islamic education from the perspective of contemporary Islamic educational philosophy, it offers a comprehensive and relevant perspective in understanding the uniqueness and excellence of Islamic education. Islamic education with a strong moral and spiritual foundation, and a focus on character development and relevance to the challenges of the times, has the potential to produce generations who are knowledgeable, have noble morals, and are able to make positive contributions to society